Green synthesis, characterization and biological activities of silver nanoparticles synthesized from Neolamarkia cadamba - Maheswari Juluri; Reshma Anjum Mohammed; Sankari Mohan; Narasimha Golla; Suresh Babu Naidu Krishna; Kishori Battini (International Association of Physical Chemists (IAPC), 2023)
Background and purpose: Metal nanoparticles are essential due to their unique catalytic, electrical, magnetic, and optical characteristics, as well as their prospective use in sensing, catalysis, and biological research. In recent years, researchers have focused on developing cost-effective and eco-friendly biogenic practices using the green synthesis of metal nanoparticles (AgNP). Experimental approach: In the present study, the aqueous extracts prepared from the leaf, stem, bark, and flower of Neolamarkia cadamba were used for the synthesis of silver nanoparticles. Synthesized silver nanoparticles were characterized using UV-Visible spectroscopy, zeta potential, dynamic light scattering, scanning electron microscope (SEM), and EDAX. Key results: The current study showed absorption of synthesized AgNPs at 425, 423, 410, and 400 nm. Dynamic light scattering of AgNPs Showed size distribution of AgNPs synthesized from leaf, stem, and flower aqueous extracts ranges from 80-200 nm and AgNPs prepared from bark extract ranges from 100-700 nm. Zeta-potential of the biosynthesized AgNPs was found as a sharp peak at -23.1 mV for the leaf, -27.0 mV for the stem, -34.1 mV for the bark, and -20.2 mV for the flower. Silver nanoparticles and crude extracts of Neolamarkia cadamba showed effective antibacterial, antifungal, and antioxidant activities. Conclusion: Silver nanoparticles have substantial antibacterial activity against Gram-positive bacteria and also exhibit the utmost antifungal activity against Aspergillus niger. The study concludes that the green synthesis of silver nanoparticles from N. cadamba leaf, stem, bark, and flower extract is a reliable and eco-friendly technique.